THE VIRTUAL RESOURCES OF A CIVIC SOCIALIZATION OF A MODERN RUSSIAN YOUTH - Magomed Azretovich Chotchaev; Marina Mihaylovna Shulga (Современная наука и инновации)
The article consideres particular qualities of a civil socialization of modern Russian youth. A particular attention is paid to the problems of influence of Internet information resources for the establishment of citizenship of young people in conditionals of institutionalization of information war as the leading technology of modern politics, the models of a demonstration of a citizenship in a virtual environment is given below.